The issue of gender stereotypes in the Convention on the Elimination of All Forms of Discrimination against Women - Frańczak, Olga (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
The article deals with the obligation to eradicate gender stereotypes stipulated in the Convention on the Elimination of All Forms of Discrimination against Women. The problem of gender stereotypes is rarely analysed in the legal literature and the role of law in forming public opinions is underestimated. Legal rules influence social views and can shape them accordingly over time. CEDAW is not the only act which deals with the issue of gender stereotypes but it deserves special attention because of the special position of the United Nations and the importance that was given to the issue of stereotypes. The article presents the circumstances of creating the Convention, as well as indicates the documents preceding it. It also describes the reservations made by states to show the specificity of the document as well as how much controversy arose around the issue. The article also includes the introduction to the entire content of the Convention and the analysis of the provisions on gender stereotypes. The obligation to eradicate gender stereotypes is shown in the context of the content of the entire Convention as well. Moreover, the obligation in question is shown in the broader context of the obligation to combat discrimination against women.
Keywords: gender; social roles; Convention on the Elimination of All Forms of Discrimination against Women; gender stereotypes; indirect discrimination; CEDAW; direct discrimination